2020
DOI: 10.3758/s13423-020-01771-2
|View full text |Cite
|
Sign up to set email alerts
|

Continuous flash suppression: Known and unknowns

Abstract: Studies utilizing continuous flash suppression (CFS) provide valuable information regarding conscious and nonconscious perception. There are, however, crucial unanswered questions regarding the mechanisms of suppression and the level of visual processing in the absence of consciousness with CFS. Research suggests that the answers to these questions depend on the experimental configuration and how we assess consciousness in these studies. The aim of this review is to evaluate the impact of different experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 193 publications
(304 reference statements)
1
43
0
Order By: Relevance
“…Awareness of the prime is prevented through constant changes in the masking stimulus or stimuli (i.e., every 100 ms) so that attention and awareness remain on this constantly changing information; thereby the name continuous flash suppression. As any technique, CFS comes with its own peculiarities, and the extent of non-conscious processing with this technique is still debated ( Pournaghdali and Schwartz, 2020 ). For example, Hedger et al (2016) applied CFS to investigate whether threat stimuli gain privileged access to awareness due to their evolutionary importance.…”
Section: Further Research With Masked Affective Stimulimentioning
confidence: 99%
“…Awareness of the prime is prevented through constant changes in the masking stimulus or stimuli (i.e., every 100 ms) so that attention and awareness remain on this constantly changing information; thereby the name continuous flash suppression. As any technique, CFS comes with its own peculiarities, and the extent of non-conscious processing with this technique is still debated ( Pournaghdali and Schwartz, 2020 ). For example, Hedger et al (2016) applied CFS to investigate whether threat stimuli gain privileged access to awareness due to their evolutionary importance.…”
Section: Further Research With Masked Affective Stimulimentioning
confidence: 99%
“…Similarly, Caruana et al (2019) reported a preserved perceptual prioritization of upright faces, compared to inverted faces, in schizophrenia-spectrum disorders. These mixed findings in the literature may be related to the use of distinct stimuli and methodology, namely suppressors, opacity manipulation, stimulus location, and low-level features (Pournaghdali & Schwartz, 2020). For instance, in the three studies showing similar suppression times (Caruana & Seymour, 2021;Caruana et al, 2019;Seymour et al, 2016), stimuli were viewed through a mirror stereoscope, while anaglyph glasses were used in our and Zhou et al (2020) study.…”
Section: Discussionmentioning
confidence: 91%
“…In particular, while there is a general agreement that lower level visual features such as stimulus orientation can be perceived unconsciously under Continuous Flash Suppression, unconscious perception of higher-level features, such as face identity or facial expression, was not demonstrated beyond reasonable doubt. For the most comprehensive recent review of Continuous Flash Suppression studies, and the controversies surrounding the results, seePournaghdali & Schwartz (2020).4 The signals in sensory areas during unconscious processing are weaker then during conscious processing. This does not contradict our hypothesis.…”
mentioning
confidence: 99%